2021
DOI: 10.3389/fpsyg.2021.657394
|View full text |Cite
|
Sign up to set email alerts
|

“Perfect Leader, Perfect Leadership?” Linking Leaders’ Perfectionism to Monitoring, Transformational, and Servant Leadership Behavior

Abstract: Despite the growing interest in perfectionism and its many facets, there is a lack of research on this phenomenon in the context of leadership. Attending to this deficit, the present study is the first to investigate the relationship between the three facets of perfectionism (self-oriented, socially prescribed, and other-oriented perfectionism) and three types of self-rated leadership behavior. In Study 1 (N = 182), leaders’ perfectionism and its association to their organizational, goal-oriented leadership be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 84 publications
(134 reference statements)
0
16
0
Order By: Relevance
“…In another study, the relationship between perfectionism (self-oriented, socially prescribed, and other-oriented perfectionism) and three types of self-rated leadership behavior (Monitoring, Transformational, and Servant Leadership) was noted. However, this relation is not clear and requires a deeper insight [ 32 ]. It should be noted that this has not been verified in relation to nursing students.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study, the relationship between perfectionism (self-oriented, socially prescribed, and other-oriented perfectionism) and three types of self-rated leadership behavior (Monitoring, Transformational, and Servant Leadership) was noted. However, this relation is not clear and requires a deeper insight [ 32 ]. It should be noted that this has not been verified in relation to nursing students.…”
Section: Introductionmentioning
confidence: 99%
“…There are limited studies analyzing the relationship between perfectionism and self-efficacy for shaping or improving leadership skills in nursing. An association between perfectionism and self-efficacy with regard to leadership skills was found between emergency medicine students [ 31 ] and the empirical study conducted with German leaders [ 32 ]. For this reason, studies looking to determine the mechanisms of a positive relationship between self-efficacy and leadership skills with high maladaptive perfectionism are required.…”
Section: Introductionmentioning
confidence: 99%
“…The leader is to serve their people. It is better to be benevolent, doing a little kindness near or at home, than go far away to burn anger (DeYoung 2020; Otto et al 2021). Being centered; everyone can attempt to do good and do all kinds of kind actions and small acts with Loving one's fellow people benevolence is a fundamental concept in a value belief system.…”
Section: Benevolence Valuesmentioning
confidence: 99%
“…Furthermore, selforiented perfectionism (Stoeber et al, 2013) and perfectionistic strivings (Stoeber and Damian, 2016;Spagnoli et al, 2021b) and concerns (Stoeber and Damian, 2016;Spagnoli et al, 2021a) have been found to be positively associated with workaholism. Moreover, other-oriented perfectionism in leaders was found to be associated with monitoring behaviors and highlighted as a barrier to building trusting relationships (Otto et al, 2021). Other results investigated the effects of the interaction between managers' perfectionism and employees' perfectionism on work addiction, revealing that employees' socially prescribed perfectionism and work addiction was strongest when a manager was perceived to be addicted to work (Morkevičiûtė and Endriulaitienė, 2022).…”
Section: Introductionmentioning
confidence: 97%